Synthesis of the biologically important dideuterium-labelled adenosine triphosphate analogue ApppI(d2) - Turhanen, Petri A. (Beilstein Journal of Organic Chemistry, 2022)
The chemical synthesis of the dideuterium-labelled ATP analogue 1-adenosin-5’-yl-3-(3-methylbut-3-en-1,1-d2-1-ol) triphosphoric acid diester (ApppI(d2)) is described. ApppI has been reported to be an important mevalonate pathway metabolite, induced by nitrogen-containing bisphosphonates used for the treatment of several diseases related to the calcium metabolism, of which osteoporosis is the most well-known. The availability of ApppI(d2) opens possibilities to quantitative measurements of ApppI in biological samples by mass spectrometry. The synthesized target compound ApppI(d2) was purified by high-performance counter current chromatography and characterized by 1H, 13C, and 31P NMR spectroscopy as well as high-resolution mass spectrometry.
Keywords: ApppI; ATP; deuterium labelling; HPCCC; mevalonate pathway; NMR; synthesis